สารยับยั้งการสลายตัวของโปรตีนในระหว่างกรรมวิธีแยกไซโตโครมบีเอฟคอมเพลกส์ : รายงานการวิจัย - มณฑล สงวนเสริมศรี (จุฬาลงกรณ์มหาวิทยาลัย, 1990)
Measurement of electron-transport activities of various plant chloroplasts shows that Lactuca indica chloroplast gives the fastest rate of electron-transport activities. In order to elucidate electron-transfer between photosystem 1 and photosystem 2, cytochrome bf cmplex of thalakoid membrane has been isolated.It was found that 10 mM Octylglucoside was the appropriate concentration for the isolation of bf complex. However, proteolytic inhibitors such as PMSF and EDTA show no effect on the absorbance ratio of cytochrome b563 to chlorophyll in various experiments. The results indicate that proteolytic inhibitors are not necessary for the preparation of cytochrome bf complex of thylakoid membrane.